2019
DOI: 10.1371/journal.pone.0212069
|View full text |Cite
|
Sign up to set email alerts
|

Emotional response in schizophrenia to the “36 questions that lead to love”: Predicted and experienced emotions regarding a live social interaction

Abstract: Evidence suggests that individuals with schizophrenia (SZ) report anticipatory pleasure deficits compared to controls and that these deficits are linked to decreased motivation to engage socially. However, these deficits have been identified via self-report measures of hypothetical pleasant stimuli, leaving it unclear whether they exist in reference to actual social situations. To address this issue, we created a live social interaction that minimized the reliance of higher-order cognitive processes. SZ and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
(50 reference statements)
4
14
0
Order By: Relevance
“…Emotional instability affects social responses and the interest and motivation of people with schizophrenia to interact with others (Kanchanatawan et al, 2017). This is supported by previous research by Martin et al (2019) which showed that persons with schizophrenia had severe emotional instability in their social interactions. Affective aspects can be trained by controlling emotions and increasing interest in recovery in people with schizophrenia (Hendler et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Emotional instability affects social responses and the interest and motivation of people with schizophrenia to interact with others (Kanchanatawan et al, 2017). This is supported by previous research by Martin et al (2019) which showed that persons with schizophrenia had severe emotional instability in their social interactions. Affective aspects can be trained by controlling emotions and increasing interest in recovery in people with schizophrenia (Hendler et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Future research may assess this generalizability in the context of anticipated and anticipatory pleasure. Future research may also assess anticipated negative affect for positive events, especially given that recent research indicates that individuals with schizophrenia anticipate more negative affect in relation to social interactions (Martin, Castro, Li, Urban, & Moore, 2019) and can feel more negative affect, compared to healthy controls, after engaging in positive mental imagery exercises (Mote & Kring, 2019). It has been shown in healthy samples that higher detail when imagining prosocial episodes can predict stronger behavioral intentions, even in the context of a negatively valenced social encounter (Gaesser, DiBiase, & Kensinger, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Anhedonia, both social and non-social, is a component of negative symptoms that has been linked to functioning impairments that are stable across the course of the disorder [7]. However, fundamental research in controlled settings shows that people with SZ have intact hedonic experience in the presence of positively-valenced stimuli [8], as well as evidence of intact hedonic experience in the presence of positive social interactions [9,10]. It may be that people with SZ experience social pleasure in-the-moment but underreport these experiences due to method features of clinical and trait-based assessments (e.g., retrospective reporting, aggregation of affective experiences over time).…”
Section: Introductionmentioning
confidence: 99%